Zinc isotope fractionation during the inorganic precipitation of calcite – Towards a new pH proxy. (1st January 2019) - Mavromatis, Vasileios; González, Aridane G.; Dietzel, Martin; Schott, Jacques
Abstract: Zinc was co-precipitated with calcite in mixed-flow reactors at 25 °C and 6.1 ≤ pH ≤ 8.5 to quantify Zn isotope fractionation between calcite and the reactive fluid. The results suggest that the difference between the isotopic composition of the solid and the fluid (Δ 66 Zncalcite-fluid = δ 66 Zncalcite − δ 66 Znfluid ) increases by about 0.6‰ as the solution pH decreases from 8.5 to 6.1. In contrast, based on Zn aqueous speciation and the theoretical values of the reduced partition function ratios for zinc species, lnβ, the isotopic fractionation between calcite and aqueous Zn 2+, Δ 66 Z n calcite - Z n 2 +, remains constant at 0.58 ± 0.05‰ over the entire pH range investigated. The constant value of Δ 66 Z n calcite - Z n 2 + suggests that irrespective of the solution pH, the same Zn aqueous species, likely free Zn 2+ ions, interacts with calcite surface sites during the growth of this mineral via ion by ion attachment. The enrichment of calcite in 66 Zn is consistent with the formation of mononuclear, inner-sphere tetrahedral Zn surface complexes at the calcite surface and the increase of Zn coordination to 6 following its incorporation in the crystal lattice with no further isotopic fractionation. Overall, the results suggest that Zn isotopic composition of natural calcite has the potential to shed light on the prevailing pH at the time of calcite formation in the geological past.